2020
DOI: 10.1186/s13195-020-00616-3
|View full text |Cite|
|
Sign up to set email alerts
|

Reduction of NgR in perforant path decreases amyloid-β peptide production and ameliorates synaptic and cognitive deficits in APP/PS1 mice

Abstract: Background: Amyloid beta (Aβ) which is recognized as a main feature of Alzheimer's disease (AD) has been proposed to "spread" through anatomically and functionally connected brain regions. The entorhinal cortex and perforant path are the earliest affected brain regions in AD. The perforant path is the most vulnerable circuit in the cortex with respect to both aging and AD. Previous data show that the origins and terminations of the perforant path are susceptible to amyloid deposition at the younger age in AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…All the behavioral tests were performed by the EthoVision XT system (Noldus, Netherlands). The Morris water maze (MWM) was performed as described in our previous studies ( Jiang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the behavioral tests were performed by the EthoVision XT system (Noldus, Netherlands). The Morris water maze (MWM) was performed as described in our previous studies ( Jiang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Passive avoidance learning was performed using a shuttle box, comprised of a brightly illuminated compartment connected to a dark compartment via a controllable door ( Jiang et al, 2020 ). The latency, frequency, and permanence time to (in) the dark compartment are the parameters for cognitive activity determination.…”
Section: Methodsmentioning
confidence: 99%
“…The excess production of Aβ is considered the initiating factor of AD, which is generated from the hydrolysis of APP via BACE-1 and γ-secretase. NgR can cause parallel changes in sAPPα and Aβ, indicating that NgR blocks APP hydrolysis (26). In contrast to these findings, Zhou et al (24) reported that the increased interaction between NgR and APP reduced the surface expression of APP and favored the processing of APP via the BACE1 pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, NgR plays an essential role in axonal and synaptic plasticity and may participate in the pathological process of AD by affecting the metabolism of amyloid precursor protein (Park and Strittmatter, 2008). Further study has demonstrated that NgR knockdown in the perforant path rescues cognitive deficits and synaptic function by decreasing the level of amyloid precursor protein and Aβ production (Jiang et al, 2020). p75NTR is a coreceptor for NgR, which mediates cellular apoptosis and survival and synapse weakening (Fahnestock and Shekari, 2019).…”
Section: Discussionmentioning
confidence: 99%